Research translation strategies to improve the readability of workplace health promotion resources. (18th November 2016) - Wallace, Alison; Joss, Nerida
Abstract : Without deliberate and resourced translation, research evidence is unlikely to inform policy and practice. This paper describes the processes and practical solutions used to translate evaluation research findings to improve the readability of print materials in a large scale worksite health programme. It is argued that a knowledge brokering and translation role, clear planning, effective communications, strong senior leadership support and strategic alignment, and mechanisms to engage practitioners and research users are key factors required to help achieve policy and practice change directly based on research evidence.